2018
DOI: 10.3390/lubricants6020045
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Rheological Characterization of New Completely Biogenic Lubricating Greases: A Comparative Experimental Investigation

Abstract: Against the background of raw material shortage and the ever-expanding environmental consciousness, the use of biodegradable greases becomes more and more important. The aim of this experimental work is to investigate the tribological response of completely biodegradable greases. Complete biodegradable lubricating greases were formulated with high-oleic sunflower oil (HOSO) and/or castor oil, and different biodegradable thickener agents such as natural cellulose fibers of different lengths and some derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It has been reported that lignin can be incorporated into various biolubricant formulations. Gallego et al, Acar et al, and Borrero-López et al demonstrated that lignin derivatives (hexamethylene diisocyanate cross-linked, epoxide, or isocyanate functionalized lignin) act as thickening agents in castor and sunflower oils. Delgado et al. showed that epoxidized lignin can be used as a thickener in castor oil biogreases exhibiting improved tribological and antiwear performance .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lignin can be incorporated into various biolubricant formulations. Gallego et al, Acar et al, and Borrero-López et al demonstrated that lignin derivatives (hexamethylene diisocyanate cross-linked, epoxide, or isocyanate functionalized lignin) act as thickening agents in castor and sunflower oils. Delgado et al. showed that epoxidized lignin can be used as a thickener in castor oil biogreases exhibiting improved tribological and antiwear performance .…”
Section: Introductionmentioning
confidence: 99%
“…In order to take a closer look at fluid friction, which occurs inside the lubricant, rheological energy densities were investigated. It represents the energy expenditure required to deform a certain lubricant volume [24]. The rotational transient flow measurements of the model greases were carried out on an MCR-102 rheometer (Anton Paar Germany GmbH, Ostfildern, Germany) by using a PP25 plate-plate system (Anton Paar Germany GmbH, Ostfildern, Germany).…”
Section: Rational Transient Flowmentioning
confidence: 99%
“…The flow limit was determined by the intersection of the logarithmically plotted curves from the storage and loss modulus. It was shown that castor oil is a suitable candidate regarding stability of produced grease and tribological characteristics such as friction coefficient [13,14,24]. Thus, castor oil was chosen as the base oil to produce the bio-based greases.…”
Section: Bio-based Grease Development and Productionmentioning
confidence: 99%
“…The cellulose pulp was also optimized in another study as a suggestion for bio-based thickener production [12]. Moreover, in [13] it was shown that bio-based greases were developed based on castor oil and high-oleic sunflower oil with cellulose fibers as thickener. In other studies, friction coefficients of developed bio-based greases were comparable to the petrochemical greases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%